Guidelines for the Management of Wet Age-Related Macular Degeneration: Recommendations from a Panel of Greek Experts. Issue 5 (May 2016) - Androudi, Sofia; Dastiridou, Anna; Pharmakakis, Nikolaos; Stefaniotou, Maria; Kalogeropoulos, Christos; Symeonidis, Chrysanthos; Charonis, Alexandros; Tsilimbaris, Miltiadis
Abstract Purpose To propose guidelines for the management of patients with wet age-related macular degeneration (wAMD), taking into account the results of large multicenter studies and clinical experience of retina experts. Method A team of retina experts developed a consensus paper after three consecutive meetings. The group was focused on guidelines to help clinical decision-making around the definition of successful treatment and the definition of non-response to therapy. Results Parameters suggestive of a successful response to treatments included: any gain in best corrected visual acuity (BCVA) or vision loss that is less than 5–10 Early Treatment Diabetic Retinopathy Study (ETDRS) letters, reduction of central retinal thickness, partial or complete absorption of subretinal fluid (SRF), reduction of intraretinal fluid, reduction of pigment epithelial detachment or restoration of the anatomy of outer retinal layers. Non-response to current treatment was considered in the case of loss of BCVA greater than 10 ETDRS letters, increased retinal edema or increase of SRF as evidenced by optical coherence tomography or new bleeding in biomicroscopy. Conclusion The introduction of anti-VEGF agents revolutionized the treatment of wAMD. Given the complexity of the disease, the emerging new agents and the difference of cases recruited in clinical trials compared to those appearing in every-day practice, it is essential to individualize treatment options taking into account the results of clinical trials.